Post-pandemic Challenges Impeding Operators’ Efforts to Sustain Foodservice Microbusinesses - Anton, Trevor Shenal; Trupp, Alexander; Stephenson, Marcus Lee; Chong, Ka Leong (Journal of Multidisciplinary in Social Sciences, 2024)
Foodservice microbusinesses are vital to the stability of economies in emerging nations. This study examines the internal and external dimensions of challenges encountered by operators of such businesses in Malaysia post-pandemic. The study adopted a qualitative approach comprising 12 semi-structured interviews involving 14 foodservice microbusiness operators. The findings indicate that foodservice microbusinesses face challenges due to individual, political, social, and economic reasons, hampering their growth and survival. Foodservice microbusinesses suffer from staffing issues relating to employee recruitment, training, and retention, rising cost of living, lack of external support, unfavorable competition, and diminishing sales performance. This study adds to the body of knowledge on challenges microbusinesses face in the context of foodservice businesses. It suggests a need for better training transfer strategies and safeguarding employee well-being, increased digitalization to capitalize on growing market trends, more inclusive support programs focused solely on aiding microbusinesses, and a stronger enforcement of business legality laws to safeguard business from unregulated competition.